Galician Rhymes in Buenos Aires: Identity in the Poetry of Avelino Díaz (1897-1971) - Fernández Salgado, Benigno (Madrygal. Revista de Estudios Gallegos, 2015)
Even though Avelino Díaz (1894-1971) was an inspired poet, he remains a complete stranger to the literature of the country he wrote for. His books, self-published in Buenos Aires, haven’t been re-edited and neither his journalistic articles nor his hundreds of poems have been systematically compiled. In the academic sphere, a biography (Freire Freire, 2002) is the only exception to this state of indifference. This contribution proposes a reading of his life and poetic works in terms of identity by using LePage and Tabouret Keller (1985) concept of “identification”.
Keywords: Galician poetry; Buenos Aires; identity; diáspora; biography